Adaptability of a Business and Superior Performance: Triad Model of Dynamic Capabilities - Sara Guerrero-Campos; Jorge Pelayo Maciel; Jaime Antero Arango Marin (Mercados y Negocios)
This study examines the relationship between business adaptability and superior performance. The researchers used Exploratory Factor Analysis and Kruskal-Wallis statistics to analyze data from a survey of 227 companies associated with a University Center. The study found that the Triad Model of Dynamic Capabilities, which includes Sense, Seize, and Transform components, explained 78.38% of the variance in business adaptability. The findings confirm the importance of Sense, Seize, and Transform capabilities in sustaining competitive advantage, as demonstrated by the observed superior performance of the organizations. The originality of the paper lies in identifying higher-order capabilities associated with business adaptability in organizations across different sectors.